Strategi Pembelajaran Sains dan Matematika Berbasis Bermain Pada Pendidikan Anak Usia Dini: Play-Based Science and Mathematics Learning Strategies in Early Childhood Education - Diajeng Aulia (Yayasan Al Islah Bungo, 2026)
Early childhood education plays a crucial role in children's development by establishing a strong foundation for logical thinking, curiosity, and problem-solving skills. These competencies can be effectively fostered through science and mathematics learning that is developmentally appropriate and implemented using a play-based learning approach. This study employed a literature review method to examine various play-based science and mathematics learning strategies in early childhood education. The data sources consisted of 20 national and international scholarly. The implementation of science and mathematics instruction, including simple experiments, the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach, the Children's Learning in Science (CLIS) approach, as well as digital- and concrete-based games. Data were analyzed using qualitative descriptive techniques involving data reduction, conceptual synthesis, and thematic categorization. The findings indicate that play-based learning enhances various aspects of early childhood development, including scientific literacy, science process skills, creativity, numeracy, higher-order thinking skills (HOTS), and 21st-century skills (4Cs). Among the identified approaches, STEAM was the most widely implemented strategy for integrating science and mathematics learning through exploration, simple project-based activities, and meaningful play experiences. The effectiveness of these strategies is supported by teachers' competence, parental involvement, and the availability of stimulating learning media and environments.